Penerapan Prinsip Akuntabilitas dan Transparansi Dalam Pengelolaan Anggaran Pendapatan dan Belanja Desa - Anggriani, Nani; Iskandar, Deni; Nurodin, Idang (Universitas Muhammadiyah Yogyakarta, 2019)
This research was aimed to find out : 1) Application of Accountability Principles in Management of Income and Village Budget. 2) Application of Transparenci Principles in Management of Income and Village Budget. 3) Supporting and Inhibiting Factors in applying the principles of Accountability and Transparency in the Management of income and Village Budgets.The variabel of this reasech was consisted of Accountability, Tranparency as independent varable and management of income and Village badgets as dependent variable. The research methode used is qualitative method with descriptive approach. This research was conducted using observation and interview techniques with the parties involved in managing the income and Village Budget. The results of the description can be seen from the comparison of Minister of Home Affairs Regulation No. 113 of 2014 with the results of realization in the field.Management of the income and Village Budget from the Planning, Implementation, Administration, Reporting and Accountability phases is broadly in accordance with the Minister of Home Affairs Regulation No. 113 of 2014 concerning Financial Management, although there are several things in Planning, Implementation, Administration, Reporting and Accountability still not suitable because human resources are less supportive